2022
DOI: 10.1097/cce.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Spiritual and Social Support Needs and Their Association With Postintensive Care Syndrome Symptoms Among Critical Illness Survivors Seen in a Post-ICU Follow-Up Clinic

Abstract: OBJECTIVES: Spiritual and social support may be key facilitators for critical illness recovery and are identified as high priority for research. Understanding the prevalence of spiritual and social support needs in critical illness survivors may guide development of targeted interventions for support, which, in turn, may improve critical illness survivor quality of life. To characterize unmet spiritual and social support needs in critical illness survivors approximately 1 month after hospital discharge and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, it highlights that this spirituality and the wider positive benefits which it might provide (i.e., a reduction in stress facilitated by hope), are important across the critical illness recovery continuum for patients and family members. Previous research has shown that spirituality and faith can play a significant role in the recovery process following critical illness [ 25 ] and both social determinants of health and spirituality have been identified as high priority areas for research in critical illness survivors [ 26 ]. Future research, therefore, should focus on any potential unmet needs in relation to spirituality and examine any relationships that spirituality and faith may have with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it highlights that this spirituality and the wider positive benefits which it might provide (i.e., a reduction in stress facilitated by hope), are important across the critical illness recovery continuum for patients and family members. Previous research has shown that spirituality and faith can play a significant role in the recovery process following critical illness [ 25 ] and both social determinants of health and spirituality have been identified as high priority areas for research in critical illness survivors [ 26 ]. Future research, therefore, should focus on any potential unmet needs in relation to spirituality and examine any relationships that spirituality and faith may have with outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, we analyzed clinical data collected 1 month after hospital discharge of adult patients in a critical illness recovery clinic who had sepsis, respiratory failure, and/or delirium during an intensive care unit (ICU) stay lasting more than 4 days . The University of Pittsburgh Institutional Review Board approved the study and waived the HIPAA authorization requirement as data were collected retrospectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although the ideal components of post-ICU follow-up clinics have not been elucidated, data support important roles of physical rehabilitation, medication management, symptom amelioration, expectation management, emotional support, and identifying patient safety threats [27,28 ▪▪ ,29,30]. Additionally, recent studies have highlighted the importance of social, spiritual, and financial support as components of care delivered in post-ICU follow-up clinics [29,31,32,33 ▪ ].…”
Section: Delivering Post-critical Illness Care Through Specialized Fo...mentioning
confidence: 99%